2022
DOI: 10.3389/fimmu.2021.772332
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Trafficking Kinetics of Rhesus Macaque Natural Killer Cells Measured by Serial Intravascular Staining

Abstract: The in vivo tissue distribution and trafficking patterns of natural killer (NK) cells remain understudied. Animal models can help bridge the gap, and rhesus macaque (RM) primates faithfully recapitulate key elements of human NK cell biology. Here, we profiled the tissue distribution and localization patterns of three NK cell subsets across various RM tissues. We utilized serial intravascular staining (SIVS) to investigate the tissue trafficking kinetics at steady state and during recovery from CD16 depletion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Therefore, partial overlap between NK clones observed in PB and tissue may be from PB contamination, especially clones detected in the spleen and liver. However, our previous studies using intravascular staining to follow immune cell dynamics in macaques ( 42 , 76 ) found very limited circulating CD45+ hematopoietic cells contaminating gut and LN biopsies. Our phenotypic analyses of NK cells in different tissues and PB revealed marked differences, even for liver or spleen, indicating the cells we obtained from all tissues have limited PB contamination.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Therefore, partial overlap between NK clones observed in PB and tissue may be from PB contamination, especially clones detected in the spleen and liver. However, our previous studies using intravascular staining to follow immune cell dynamics in macaques ( 42 , 76 ) found very limited circulating CD45+ hematopoietic cells contaminating gut and LN biopsies. Our phenotypic analyses of NK cells in different tissues and PB revealed marked differences, even for liver or spleen, indicating the cells we obtained from all tissues have limited PB contamination.…”
Section: Discussionmentioning
confidence: 89%
“…We demonstrated groups of balanced/un-biased CD56+ NK clones and DN NK clones contributing equivalently in PB CD56+ NK compared to tissues, suggesting a shared clonal repertoire between those populations. We recently utilized serial intravascular staining (SIVS) with multi-color labeled CD45 antibodies immediately binding to circulating blood cells to study movement of blood immune cells in and out of tissues ( 42 , 76 ). We found that PB CD56+ and DN NK cells have a shorter residence time in blood and traffic more often between PB and tissues such as lymph nodes compared to the CD16+ NK subset, which remains primarily within the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower percent of CD56 bright NK cells likely reflects a shift in the distribution and trafficking patterns of NK cells, with more CD56 bright NK cells remaining resident in tissue [71][72][73][74]. This NK cell subset can also egress from the vasculature more readily than other NK cells and return back to tissue, including to lymph nodes and the liver.…”
Section: Discussionmentioning
confidence: 99%